Simultaneous quantification of rDNA methylation and copy number: Constraints to natural variation in humans and cell lines - Stephen Flint Smith; Bernardo Lemos (PLoS ONE, 2025)
Ribosomal DNA (rDNA) copy number (CN) varies widely both across and within species. In humans, it has been hypothesized that rDNA transcriptional activity is partially regulated by rDNA methylation status. Here we describe a rapid and scalable approach for the simultaneous detection of methylated and unmethylated rDNA copy number using a well characterized digital PCR technology. The linear range for detecting rDNA CN and methylation is from 0.3 ng to 20 ng DNA with a practical range from 1.25 to 15 ng DNA and can be normalized with a single copy gene, ACTB, to reflect copies per genome. Our approach detects 28S rDNA methylation using a modified methyl-specific/bisulfite PCR targeting a region with at least four CpGs. In a population of healthy donors, we observed wide variation in both methylated and unmethylated rDNA CN, as well as in the percentage of methylated rDNA copies. We found significant correlations between the total rDNA CN and both methylated rDNA CN and percent methylated rDNA CN. Individuals with a greater number of rDNA copies had more methylated copies and a higher percentage of methylated copies. The methylated rDNA CN percentage varied widely across individuals and ranged from 9% to 69% of the total rDNA copies being methylated. Finally, four human cell lines (BEAS-2B, HeLa, MCF-7, MDA-MB-231) also displayed wide differences in methylated and unmethylated rDNA CN. Overall, this method provides a new tool to study the relationship between rDNA CN and methylation while offering insight into rDNA methylation variability and the regulation of active rDNA copies.